Designing and implementing a resilient immutability mechanism for enhanced supply chain management in E-healthcare systems - Singla, Deepak; Kumar, Sanjeev; Gulzar, Yonis; Mir, Mohammad Shuaib; Gupta, Deepali; Jaziri, Wassim; Sassi, Najla; Arora, Shweta (Frontiers in Sustainable Cities, 2024)
Counterfeit drugs pose significant health risks due to their variable efficacy and potential harmful ingredients. To combat this issue, a reliable and secure track-and-trace system is essential for pharmaceutical supply chains. This paper proposes an Immutable and Decentralized Pharma (IDP) model, leveraging blockchain technology to ensure the safe and efficient distribution of medications. The IDP model utilizes smart contracts to record transactions between entities onto a blockchain, enabling end-to-end product tracking and provenance. Experimental results on a polygon blockchain test network demonstrate the feasibility and enhanced security of the IDP model in a collaborative environment. Our solution addresses the challenges of data privacy, openness, and authenticity inherent in centralized track-and-trace systems, providing a promising approach to eliminate counterfeits and guarantee product safety in pharmaceutical supply chains.